Advances in understanding of pathogenesis of aHUS and HELLP - Celia J. Fang; Anna Richards; M. Kathryn Liszewski; David Kavanagh; John P. Atkinson (2008)
Both atypical haemolytic uraemic syndrome (aHUS) and the HELLP syndrome (haemolytic anaemia, elevated liver enzymes, and low platelets) are thrombotic microangiopathies characterized by microvascular endothelial activation, cell injury and thrombosis. aHUS is a disease of complement dysregulation, specifically a gain of function of the alternative pathway, due to mutations in complement regulatory proteins and activating components. Recently, the same complement mutation identified in multiple patients with aHUS was found in a patient with the HELLP syndrome. The pathogeneses of both diseases are reviewed focusing on the role of the complement system and how its dysfunction could result in a thrombotic microangiopathy in the kidney in the case of aHUS and in the liver in the case of the HELLP syndrome.